Alternative Logistics Systems for Enhancing Competitiveness of Rice in Chiang Mai, Chiang Rai and Phayao Provinces - พันธุ์มณี, ชนิตา; กุณาศรี, เกษม; ตันสุชาติ, เริงชัย (Community and Social Development Journal, 2018)
This research aims to construct the models of alternative logistics systems for enhancing the competitiveness of rice in the target areas; Chiang Mai, Chiang Rai and Phayao provinces, and analyze the value gain of the alternative logistics systems. The samples are 300 farmers in Chiang Mai, Chiang Rai and Phayao provinces selected by quota and multi-stage sampling approaches. Moreover, 20 stakeholders in the rice logistics are selected by snowball sampling method. The participatory action research (PAR) and the analytical hierarchy process (AHP) analysis are used as the research tools. The result brings about the integrated model between lean logistics of rice focusing on minimized cost and green logistics of rice stressing on lowest GHG emission. The first ranking model selected is the rice logistics using alternative energy by changing diesel fuel to NGV and LPG gases. Finally, the value gains of alternative logistics express that both options of alternative energy are worth in financial and environmental aspects.